Longitudinal analysis of leisure noise exposure among adolescents with special focus on portable listening devices: the OHRKAN cohort study. (2nd December 2018) - Dreher, Annegret; Weilnhammer, Veronika; Gerstner, Doris; Hendrowarsito, Lana; Twardella, Dorothee; Reiter, Christina; Perez-Alvarez, Carmelo; Steffens, Thomas; Herr, Caroline; Heinze, Stefanie
ABSTRACT: The aim was to investigate leisure noise exposure and sociodemographic determinants of risky leisure noise exposure over five years in 2148 students visiting grade 9 of any school type in a German city from 2009–2011. Within the OHRKAN cohort study, leisure noise exposure was calculated from literature-retrieved sound pressure levels (SPLs) and self-reported duration of 18 leisure activities at baseline and two follow-ups. Risky exposure was defined as exceeding 85 dB(A) averaged over a 40-h-week. Determinants of risky total leisure noise (TLN) exposure and risky exposure to portable listening devices (PLDs) were investigated using generalised estimating equations (GEEs). Up to 73% of students exceeded noise levels of 85 dB(A) at some timepoint. The noise exposure and importance of different leisure activities changed with increasing age. Risky exposure to TLN and PLDs was associated with lower education, single parent households and being male. Risky PLD exposure was additionally associated with a migrant background. Current prevention measures for leisure noise exposure must be extended to at-risk groups. Besides enhancing campaigns in lower education schools, acoustical insulation in sports halls, noise warnings on tools or in videogames could address especially men. Migrants need education about healthy PLD use in their native language if necessary.